UK policies and industrial stakeholder perspectives on building thermal performance. (February 2019) - Ling-Chin, J.; Taylor, W.; Davidson, P.; Reay, D.; Tassou, S.; Roskilly, A.P.
Abstract: Improving building thermal performance is important if the UK is to meet the 80% emission reduction target by 2050. Aiming to provide insights into UK building thermal performances, relevant national policies were highlighted and a one-day workshop was run. Real-time responses of industrial stakeholders were collected using Poll Everywhere. The stakeholder perspectives on challenges, barriers, thermal performances and other concerns were reported. It showed that (i) a whole-house retrofit plan was necessary; (ii) improving thermal performances would be challenging but achievable; and (iii) industrial stakeholders were concerned about building performance, legislation, drivers, cost, professional development, technology alternatives and future vision. It was concluded that industrial consultation should be continued to assist thermal performances of buildings in the UK.